E-cadherin signal sequence disruption: a novel mechanism underlying hereditary cancer - Joana Figueiredo (Molecular Cancer, 2018)
Abstract The aim of this study was to uncover the pathogenic relevance and the underlying molecular mechanism of a novel CDH1 variant found in a Hereditary Diffuse Gastric Cancer family (p.L13_L15del), which affects the signal peptide of E-cadherin without changing the remaining predicted sequence. We verified that p.L13_L15del cells yield low levels of E-cadherin, decreased cell adhesion and enhanced cell invasion. Further, we demonstrated that the disruption of the highly conserved hydrophobic core of the signal peptide hampers the binding of cellular components crucial for E-cadherin translation and translocation into the endoplasmic reticulum, constituting a new molecular basis for the loss of a tumour suppressor gene causative of hereditary cancer.